Minor alleles of FTO rs9939609 and rs17817449 polymorphisms confer a higher risk of type 2 diabetes mellitus and dyslipidemia, but not coronary artery disease in a Chinese Han population - Zhang, Youjin; Chen, Lvlin; Zhu, Junchen; Liu, Hao; Xu, Luying; Wu, Yang; He, Chuan; Song, Yongyan (Frontiers in Endocrinology, 2023)
Background: Relationships of the polymorphisms in fat mass and obesity-associated gene (FTO) and peroxisome proliferator-activated receptor delta gene (PPARD) with metabolic-related diseases remain to be clarified.One thousand three hundred and eighty-one subjects were enrolled.Metabolic-related diseases including obesity, dyslipidemia, hyperhomocysteinemia, hyperuricemia, hypertension, type 2 diabetes mellitus (T2DM) and coronary artery disease (CAD) were defined based on diagnostic criteria. FTO rs9939609 and rs17817449, and PPARD rs2016520 and rs2267668 polymorphisms were genotyped by using polymerase chain reaction-restricted fragment length polymorphism method.Results: Patients with T2DM or dyslipidemia had a higher frequency of AA, AT or AA + AT genotypes as well as A allele of FTO rs9939609 polymorphism than those free of T2DM or dyslipidemia (P ≤ 0.04 for all). Patients with T2DM or dyslipidemia had a higher frequency of GG, GT or GG + GT genotypes as well as G allele of FTO rs17817449 polymorphism than those free of T2DM or dyslipidemia (P ≤ 0.03 for all).Multivariate logistic regression analyses showed that FTO rs9939609 and rs17817449 polymorphisms were independently associated with T2DM as well as dyslipidemia after adjustment for age, sex, smoking and other metabolic diseases. FTO rs9939609 and rs17817449 polymorphisms were not associated with obesity, hyperhomocysteinemia, hyperuricemia, hypertension and CAD. Obese or T2DM carriers of the AA or AT genotype of the FTO rs9939609 polymorphism had a higher prevalence of dyslipidemia compared to non-obese or non-T2DM carriers of the AA or AT genotype (P = 0.03 for both). Among the carriers of GG or GT genotype of the FTO rs17817449 polymorphism, the prevalence of dyslipidemia in obese patients was higher than that in non-obese subjects (P < 0.01). PPARD rs2016520 and rs2267668 polymorphisms were not correlated with any of the metabolic-related diseases in the study population.Minor alleles of FTO rs9939609 and rs17817449 polymorphisms confer a higher risk of T2DM and dyslipidemia, and the risk is further increased among obese individuals. PPARD rs2016520 and rs2267668 polymorphisms are not associated with metabolic-related diseases.